kamulaştırmasız el atma - Akkan, Bahattin (My University, 2004)
Soyadı: Bahattin Akkan Kamu Yönetimi Mahalli İdareler ve Yerinden Yönetimler Memiş Tez Türü ve Tarihi: Yüksek Lisan – Ağustos 2004 Kamulaştırma, Kamulaştırmasız El Atma

KAMULAŞTIRMASIZ EL ATMA Mülkiyet hakkı insanın en temel haklarından biridir. Günümüz çağdaş devletlerinde bu hak kanun ve anayasalarla güvence altına alınmıştır. Ancak sosyal devlet anlayışının gelişmesi ve devletten beklenen hizmetlerin çok artması karşısında idare bu hizmetleri yerine getirebilmek için insanın temel haklarından olan mülkiyet hakkına bazı sınırlar koymaktadır. Böylece, bireyin menfaati ile toplumun menfaati çatıştığında toplumun menfaati üstün tutulmaktadır. İşte idare, bu hizmetleri yerine getirirken kendisi için gerekli olan taşınmazları satın alarak bu hizmetleri yapar, ama bu her zaman yeterli olmamaktadır. Bu nedenle idare bireyin rızası dışında bir yöntemle ihtiyaç duyduğu taşınmazı karşılığını ödeme yoluyla kamulaştırma yapmaktadır. Kamulaştırma işleminin uzun ve idarenin ihtiyacının acil olması durumlarında idare yine bireyin rızası dışında onun taşınmazına hiçbir karşılık ödemeden el atmaktadır. Kamulaştırmasız el atmanın herhangi bir hukuki bir niteliği yoktur. Bu nedenle idarelerin bu yolu çok kullanmaması gerekmektedir. Aksi halde, bireyin en temel haklarından biri olan mülkiyet hakkı çiğnenmiş olacaktır. İdarenin işlemlerine karşı yargı yolu açık olduğundan bu işlemlere karşı iptal ve tazminat davası açılmaktadır. Yine bu konuda Türkiye aleyhine İnsan Hakları Avrupa Mahkemesinde birçok dava açılmıştır. Bu nedenle mevcut yasal düzenlemelerde birçok değişiklik yapılmıştır. Name and Surname: Bahattin Akkan Major : Public Administration Program :.Municipal Administrations and Provincial Governments Thesis Adviser: Associate Prof. Dr. Emin Memiş Type and Date of Thesis: Master of Administration- August 2004 Key Words: Confiscation, Grab without Confiscation SUMMARY GRAB WITHOUT CONFISCATION Property right is one of the most fundamental human rights. This right is guaranteed by laws and constitutions in modern states of today. However, in response to development of social state conception and increase in services expected from the state, the governments put some limitations to the property right, which is one of the most basic human rights. In this manner, when individual rights and the rights of the public conflict, the rights of public are put before the individual ones. The administration works by purchasing the immovable necessary for executing these services; however, this cannot always meet the requirements. For this reason, the administration confiscates the immovable it needs through a method out of consent of the individuals by paying in return for the property under consideration. In case that the confiscation procedure necessitates long time and the need of the administration for the property is urgent, the administration grabs the property again out of the consent of the possessor but without paying for it this time. Grabbing without confiscation does not have any legal attribute. Therefore, the governments should not often apply this way. Otherwise, the property right, which is one of the most primary individual rights, might be violated. Since the way to the adjudication against administrative acts is open, it is possible to bring an action for rescission and to sue for damages. There are many related lawsuits brought against Turkey to the European Court of Human Rights. That's why several changes have been made in the existing legal regulations.
Keywords: Kamulaştırma